The Influence Of Service Quality And Hospital Image For Patient Satisfaction And Loyalty Dental And Oral Hospital In Jakarta - Soen, Ricky Chandra Jaya; Kristaung, Robert (International Journal Labs, 2023)
This study aims to analyze the effect of service quality and hospital image on patient satisfaction and loyalty of Dental and Oral Hospital in Jakarta. The research method used is a quantitative method with primary data from 200 patients who have or are receiving treatment at RSGM Jakarta. Non-probability sampling technique in the form of purposive sampling was used to take samples in this study using a Google Form questionnaire. Analysis of each research variable was carried out with SPSS version 25 and analysis of the influence between variables was carried out using Structural Equation Modeling (SEM). The results of the study stated that there were several hypotheses that had a positive effect including; (H1) The hospital's image of patient satisfaction; (H2) Quality of service for patient satisfaction; (H4) The hospital's image of patient loyalty; (H5) Quality of service for patient loyalty; (H6) The hospital's image of patient loyalty through patient satisfaction; (H7) Quality of service to patient loyalty through patient satisfaction. The conclusion in this study is that patient satisfaction does not have a positive effect on patient loyalty. This research is used as evaluation material for the management of the Dental and Oral Hospital to make various innovations to improve the quality of service and the image of the hospital in order to shape patient satisfaction to gain patient loyalty.